The intelligent portfolio : practical wisdom on personal investing from Financial Engines - Jones, Christopher L., 1967- (J. Wiley & Sons, 2008)
This is a must-read book on making informed and confident decisions with your nest egg. "The Intelligent Portfolio" is an easy-to-read guide to intelligent personal investing drawing upon the insights of Financial Engines (FE) - a leading independent investment advisor founded by Nobel Prize-winning economist William F. Sharpe that makes advice available to millions of retirement plan investors at America's largest companies. In this book, FE Chief Investment Officer Christopher Jones uses state-of-the-art simulation and optimization methods to demonstrate the often-surpr- ising results of applying modern financial economics to personal investment decisions. By illustrating the realistic range of possible investment outcomes, Jones reveals how today's decisions impact future results and helps investors maximize their chances of reaching goals. Challenging conventional wisdom that often leads novice and experienced investors astray, "The Intelligent Portfolio" discloses the most important factors for investment success using insights familiar to large pension funds, foundation- s, and endowments, but often mysterious to individual investors. Sp- ecifically, readers will discover how to: avoid common investing mistakes; prioritize the most important factors to simplify decisions; understand the tradeoffs that underlie investment choices; build high performing portfolios; critically evaluate the investment advice they receive; and much more